Relationship of Personal Hygiene and Environmental Conditions with Complaints of Skin Disease - Sumantri Alikhan Sains (Universitas Mandala Waluya, 2021)
Based on data from the Tikep Health Center, for the last three years Waturempe Village has become the village with the highest incidence of skin diseases and accounts for almost 50% of skin diseases. The aim of this study was to determine the relationship between personal hygiene and environmental conditions in Waturempe Village. The population in this study were all heads who live in Waturempe Village as many as 120 heads of families (KK). The sample size was 92 respondents, taken by simple random sampling. The data were obtained using a questionnaire then analyzed descriptively and inferentially using the chi square test. The results showed that there was a strong relationship between personal hygiene (X²hit=39,21 2> X²tab = 3,841), moisture (X²hit=36,655 > X²tab=3,841), temperature (X²hit=45,126 > X²tab=3,841), natural lighting (X²hit=29,362> X²tab=3,841), and occupancy density (X²hit=27,273 > X²tab=3,841) with complaints of skin diseases. There was a moderate relationship between water quality and complaints of skin diseases (X²hit=19,354 > X²tab=3,841). It is expected that the community always maintains personal hygiene and improves condition of the home environment and is always aware of the transmission of skin diseases.